Making Posters - Gary Hermance; Nancy Johnson (EDIS)
This document is 4HGCM60 of the Florida 4-H Youth Development Program, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Printed, October 1989; Reviewed June 2002.